El premio por riesgo de mercado: estimación para Chile - Maquiera, Carlos P. (2019)
The Capital Asset Pricing Model (CAPM), developed in the early 1960s, is still today the main model for estimating the performance required for a financial asset by a well-diversified investor. The estimation of its main variables, the return of the risk-free asset and, to a greater extent, the premium for the expected risk of the market portfolio, have been the subject of much controversy and debate, particularly when it comes to estimating them for emerging markets. This paper reviews the existing literature related to the estimation of the premium for expected risk, also known as risk premium, both in general terms, and as applied to emerging markets, in order to formulate and suggest an estimated value of such variable for the case of Chile.